UTILIZATION OF Moringa oleifera SEEDS AS A NATURAL COAGULANT IN REDUCING TOTAL COLIFORM BACTERIA AND Escherichia coli (E. coli) IN ANIMAL SLAUGHTERHOUSE WASTEWATER - Nurhidayah Nurhidayah; Candra Dwi Ratna; Hery Setyobudiarso (Department of Environmental Engineering-Faculty of Civil, Planning, and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2026)
Livestock slaughterhouse wastewater has the potential to pollute the environment because it contains pathogenic bacteria, especially Escherichia coli and total coliform, which are indicators of fecal contamination. This study aims to analyze the effect of varying doses of natural coagulant from moringa seeds (Moringa oleifera) on the reduction of E. coli and total coliform in RPH wastewater with a settling time of 40 minutes. The method used was coagulation-flocculation with varying coagulant doses of 150 gr, 200 gr, and 250 gr, followed by a sedimentation process. Microbiological analysis was conducted to determine the number of E. coli and total coliform bacteria, with each treatment repeated three times. The results showed that increasing the dose of moringa seed coagulant affected the reduction in the number of bacteria. For the total coliform parameter, the number of bacteria decreased from 11,500 MPN/mL at a dose of 150 gr to 6,100 MPN/mL at a dose of 250 gr. Meanwhile, the number of E. coli decreased from 3,100 CFU/mL to 1,550 CFU/mL at the same dose. These results indicate that moringa seeds have the potential to be used as an effective, simple, and environmentally friendly natural coagulant in reducing pathogenic bacterial contamination in slaughterhouse wastewater.